Evaluating SIMPUS Implementation at Teladan Community Health Center: a HOT-Fit Framework Analysis - Sri Lestari Ramadhani Nasution; Ermi Girsang; Ahmad Fuadi Nasution (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Community Health Centers are required to implement a Community Health Center Information System (SIP) in accordance with Minister of Health Regulation No. 31 of 2019. Medan Teladan Community Health Center has implemented various information systems, one of which is e-Puskesmas, but still found obstacles. This study aims to evaluate the implementation of the Management Information System (SIMPUS) at Medan Teladan Community Health Center using the Human Organization Technology (HOT)-Fit method. This type of research is descriptive qualitative research. The study was conducted at Medan Teladan Community Health Center starting from December 2024 - July 2025. Informants in this study were 5 people consisting of the head of the community health center and medical record officers as key informants, registration officers, SP2TP officers and pharmacy service officers as supporting informants. Data analysis was carried out by data reduction, data presentation and drawing conclusions to identify relevant finding patterns in each aspect of HOT-Fit. The results of the study obtained an evaluation of the implementation using the HOT-Fit method on the human aspect, the user side has problems with input errors, where around 60% of informants reported data input. Organizational aspects, the organizational structure is in place, monitoring and evaluation have been carried out and guidelines for using the information system are in place even though they only adopt those from the Ministry of Health. Technology aspects, the quality of the system is still not optimal because the system has not been integrated with all programs and frequent server disruptions or data bridging failures, differences were also found between drug data in the system and actual stock in the pharmacy warehouse. Net benefit aspects, this system has succeeded in reducing dependence on manual processes and increasing data accuracy, but data integration across all programs is still an obstacle. It is recommended to the Medan City Health Office to encourage the integration of information systems between programs into one platform and ensure server stability. Keywords: System evaluation, information system, HOT-Fit